2019
DOI: 10.1021/acsami.9b07161
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Evaluation of Surface Potential Characteristics on Mesenchymal Stem Cells’ Osteogenic Differentiation

Abstract: The surface electric potential of biomaterials has been extensively proven to play a critical role in stem cells’ fate. However, there are ambiguous reports on the relation of stem cells’ osteogenic capacity to surface potential characteristics (potential polarity and intensity). To address this, we adopted a surface with a wide potential range and both positive/negative polarity in a comprehensive view to get insight into surface potential-regulating cellular osteogenic differentiation. Tb x Dy1–x Fe2 alloy/p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 34 publications
0
41
0
Order By: Relevance
“…At the same time, considering the effect of surface potential on the cell microenvironment, a moderate surface potential intensity can establish the optimal integrin-binding state to produce the strongest osteogenic differentiation behavior. [15] Therefore, we speculated that the membranes with 200 µm positive and negative response repeat length might receive the optimal electrical activity. The piezoelectric coefficients of the membrane change in a chordal function along the repeating direction (Figure 1I), which was consistent with the PFM response.…”
Section: Characterization Of Cfo/(pvdf-trfe) Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, considering the effect of surface potential on the cell microenvironment, a moderate surface potential intensity can establish the optimal integrin-binding state to produce the strongest osteogenic differentiation behavior. [15] Therefore, we speculated that the membranes with 200 µm positive and negative response repeat length might receive the optimal electrical activity. The piezoelectric coefficients of the membrane change in a chordal function along the repeating direction (Figure 1I), which was consistent with the PFM response.…”
Section: Characterization Of Cfo/(pvdf-trfe) Membranesmentioning
confidence: 99%
“…differentiation ability of cells, studies have shown that the positive and negative changes of the surface potential can also improve the osteogenic differentiation ability of cells by regulating the conformation of adsorbed proteins, intracellular and extracellular ions and the activation state of integrins. [15,16] In other words, the surface electrical properties of the material would regulate the integrin state of the cell-material interface and cell ion channels, thereby inducing the rearrangement of the cytoskeleton and mediating the osteogenesis-related signal cascade, eventually enhancing bone tissue regeneration. [17] Although P(VDF-TrFE) can indeed promote rapid bone formation in situ, it still needs to be reasonably designed to maximize its electrical activity for future clinical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, OCA tightly integrates with cells and peptide via Schiff’s base reaction can also enhance osteo-inductive effect of sCT. Another important factor on osteogenic differentiation is the negative charge, rooting in carboxyl groups on the backbone of alginate, which can induce intracellular calcium ions to deposit in the extracellular matrix . These results reveal that sCT-OCA-HPCH, with optimal osteogenic induction, can enhance ALP activity, promote osteoblasts to absorb calcium from surrounding microenvironment, and assist calcium deposition outside of the osteoblasts.…”
Section: Resultsmentioning
confidence: 91%
“…The role of electrical stimulation on cellular growth behavior could be attributed to the change of intracellular Ca 2+ concentration upon the applied surface electric field to activate calcium‐mediated PKC upstream signaling pathway, finally regulate the osteogenic differentiation 23,27‐29 . And the regulating mechanism on polarized P(VDF‐TrFE) is illustrated as: the surface charges modulates the adsorption conformation of fibronectin, changes the binding of integrin receptors, affects both of the formation of focal adhesion complexes and the activation of the FAK/ERK upstream signaling pathway 22,30,31 …”
Section: Discussionmentioning
confidence: 99%